Power relations and agrarian struggles in coffee-growing regions: questions and reflections. - Samper Kutschbach, Mario (Revista de historia., 1994)
If we analyze and compare agrarian structures and social relations in historical-geographical areas where coffee has long been the main cash crop, rather than any uniformity or similarity, what stands out is a remarkable heterogeneity in terms of the types of productive units and the links of association or conflict between collective actors in these areas. However, it is not only a question of interregional variations, but also of profound transformations within the same area from one period to another, e.g., through processes of concentration or subdivision of property, gradual or abrupt transitions from one type of labor to the predominance of another, changing power relations that give rise to new alliances and confrontations, etc.